2019
DOI: 10.3847/1538-4357/ab33ff
|View full text |Cite
|
Sign up to set email alerts
|

Fast Recursive Reconnection and the Hall Effect: Hall-MHD Simulations

Abstract: Magnetohydrodynamic (MHD) theory and simulations have shown that reconnection is triggered via a fast "ideal" tearing instability in current sheets whose inverse aspect ratio decreases to a/L ∼ S −1/3 , with S is the Lundquist number defined by the half-length L of the current sheet (of thickness 2a). Ideal tearing, in 2D sheets, triggers a hierarchical collapse via stretching of X-points and recursive instability. At each step, the local Lundquist number decreases, until the subsequent sheet thickness either … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…They numerically showed in this case the asymptotic growth rate of the tearing instability is Alfvénic, independent of the Lundquist number and the ion inertial length itself. Shi et al (2019) performed a series of Hall-MHD simulations, testing the results for the primary reconnection site onset discussed in Pucci et al (2017). Shi et al (2019) focused on how the Hall effect modifies the recursive collapse trigger of reconnection.…”
Section: The Hall Effectmentioning
confidence: 99%
See 4 more Smart Citations
“…They numerically showed in this case the asymptotic growth rate of the tearing instability is Alfvénic, independent of the Lundquist number and the ion inertial length itself. Shi et al (2019) performed a series of Hall-MHD simulations, testing the results for the primary reconnection site onset discussed in Pucci et al (2017). Shi et al (2019) focused on how the Hall effect modifies the recursive collapse trigger of reconnection.…”
Section: The Hall Effectmentioning
confidence: 99%
“…Shi et al (2019) performed a series of Hall-MHD simulations, testing the results for the primary reconnection site onset discussed in Pucci et al (2017). Shi et al (2019) focused on how the Hall effect modifies the recursive collapse trigger of reconnection. They showed that the reconnection rate, the dissipation property and the power spectra are modified significantly.…”
Section: The Hall Effectmentioning
confidence: 99%
See 3 more Smart Citations